"The More Support You Have the Better": Partner Support and Dyadic HIV Care Across the Continuum for Gay and Bisexual Men. (1st May 2015) - Goldenberg, Tamar; Stephenson, Rob
Abstract : Background: Gay, bisexual, and other men who have sex with men account for a disproportionate burden of HIV incidence in the United States, with one-third to two-thirds of these new HIV infections occurring within main partnerships. Early initiation and adherence to highly active antiretroviral treatment is a key factor in treating and preventing the transmission of HIV; however, the average rate of adherence in the United States is low. Social support has been examined as a source of improving health for people experiencing a variety of chronic health conditions. This study aims to understand perceptions of how dyadic HIV care could influence partner-specific support for same-sex male couples with a goal of improving adherence. Methods: Data were collected from 5 focus group (n = 35) discussions with gay and bisexual men in same-sex male relationships in Atlanta, GA. Participants discussed perceptions of how dyadic HIV care would impact partner support among serodiscordant and seroconcordant HIV-positive same-sex male couples. Verbatim transcripts were segmented thematically and systematically analyzed to examine patterns. Results: Participants described how dyadic HIV care can facilitate emotional, informational, and instrumental support at various stages across the continuum of care, depending on partner dynamics. Participants stated that dyadic HIV care can provide an additional "sense of togetherness" and "solidarity" that helps to "alleviate stress." Conclusions: Results suggest that dyadic approaches for HIV care across the continuum may be useful in promoting partner support and improving adherence. Future research should further examine dyadic interventions for HIV treatment among same-sex male couples.